Portal de Periódicos Científicos Eletrônicos da Universidade Federal da Paraíba: estado da arte e subsídios para estabelecimento de uma política - Paiva, Maria José Rodrigues (2018)
Periodicals need to meet certain requirements and standardizations, these in turn, enable their insertion and permanence of in relevant and qualifying databases. Thus, the main idea of this work is to investigate management practices on behalf of the Portal of Electronic Scientific Periodicals, of the Federal University of Paraíba in João Pessoa-Brazil. The research dealt with periodical inclusion policy, information dissemination and visibility and promotion issues, especially considering those present in: A1, A2, B1 and B2 strata regarding periodicals connected to Postgraduate studies. The research also dealt with the identification of research development agencies. The work identifies the requirements made by the DOAJ, RedALyC, LATINDEX, INDEX COPERNICUS, and SPELL (ANPAD) databases, regarding the acceptance of periodicals. The work presents concepts about State, public policies and scholarly production, points out historical aspects on the emergence of universities, modernization of higher education and post-graduation, and the path to scientific publication. The research is of applied, exploratory nature, uses a qualitative method and presents a case study, applies a monographic method with the use of documental and bibliographic procedures. Dialectical Materialism is used in order to understand the dynamics of the aforementioned Portal and the existing contradictions. The difficulties and/or facilities pointed out by editors when submitting a periodical to the Portal were emphasized as well as aspects related to management practices of the participating Postgraduate Programs of in the Federal University of Paraíba regarding those who were classified in Qualis 2017 indicators. The information gathered was analyzed via qualitative dialogical method. Data collection was done through a questionnaire. It was possible to identify that: a) periodical inclusion policy is incipient in the Portal b) editors demonstrate difficulties to comply with the rules required to include periodicals in the Portal and c) absence of a professional librarian to conduct the insertion process in national and international Databases. At the same time, this research presents suggestions for institutionalization and management of the Portal at the Federal University of Paraíba and indicates and annexes normative documents that rule Scientific Periodical Portals used in similar institutions such: UFPE, UFRN, UFRGS and UFSC. Lastly, it offers a Glossary of terms that refer to the production area of scholarly journals.